Implementation of time efficient hybrid multiplier for FFT computation - Nikhil, R; V. S. Veerendra, G; Rahul M. S. Sri Harsha, J; V. S. V. Prabhakar, Dr (International Journal of Engineering and Technology, 2018)
Now a days in designing a VLSI circuits we are coming across many problems such as high power intake, delay and large utilization of chip area in order to overcome these problems a new architectures are developed. In our project we deals with FFT computation which internally involves series of multiplication and addition therefore requirement of efficient multipliers is needed and therefore we come across two high speed improved multipliers Booth multiplier and Wallace tree multiplier which are good in terms of power efficiency and low output delay. The main aim of our project involves hybridizing the both Wallace multiplier and Booth multiplier which yields low delay and low power consumption than compared to individual multipliers. The Booth multiplier is used for reduction of partial products and for addition operations carry save adders is used in Wallace tree multipliers and thus hybrid is designed by combining both the algorithms which in turn produces better results and they can be observed in comparisons tabular column in our documentation. These multipliers can be designed in many ways such using cmos layout techniques and also using Verilog programming and we have chosen Verilog programming which requires Xilinx software and codes are developed in gate level design model for the respective multiplier models and the results will be tabulated.Â Â